An introduction to Iranian Collembola (Hexapoda): an update to the species list - Masoumeh Shayan Mehr; Elliyeh Yahyapour; Morteza Kahrarian; Elham Yoosefi Lafooraki (ZooKeys, 2013)
The Collembola fauna of Iran is little known and no comprehensive examination of this group of Hexapoda is available for this region. The only notable work on Collembola was carried out by Cox (1982). Recently, studies on the Collembola fauna have started in several regions. In this paper, publications by different researchers are documented and the species that have been found in different regions of Iran until January 2013 are listed. At present, 112 species, belonging to 18 families and 57 genera are known from Iran.